The Impact of Capital Structure and Corporate Governance on Firm Performance: Evidence from Chinese Listed Manufacturing Firms - QI, ZHAN (2019)
This paper uses a panel data of 1872 manufacturing companies listed in the Shanghai and Shenzhen Stock Exchanges of China from 2009 to 2018, examining the impact of capital structure and corporate governance on firm performance. The empirical test finds that the leverage ratio irrelevant to the corporate performance, and firms with high ownership concentration or government ownership tend to achieve better business performance in terms of Tobin’s Q, but no evidence proved that there was a significant connection between managerial shareholding and the firm value. Concerning about board structure, the bigger size of the board associated with the improvement of corporate performance. Besides, every additional independent director joins on the board tend to harm firm performance. However, role duality of CEO seems insignificant connected with the firm performance. In addition, sales growth and the proportion of tangible assets is irrelevant to Tobin’ Q value, but there is a positive linkage between firm size and firm performance, large-scale firms tend to have better business performance.